The Development of Summary Writing Skills Using a Computer-Assisted Instructional Module for Matthayomsuksa 1 Students at Kalasin College of Dramatic Arts - Deelao, Kittitat; Sribunrueang, Pacharakit; Phrakrukhamphithammanuwat (Journal of Buddhist Education and Research (JBER), 2026)
This research aimed to: 1) develop a lesson plan for summary writing skills using Computer-Assisted Instruction (CAI) with an efficiency criterion of 80/80; 2) compare students’ learning achievement in summary writing before and after instruction; and 3) examine students’ satisfaction with the developed lesson plan. The sample consisted of 30 Grade 7 students at Kalasin College of Dramatic Arts during the second semester of the 2024 academic year. The research instruments included lesson plans for summary writing using Computer-Assisted Instruction, an achievement test, and a student satisfaction questionnaire. Data were analyzed using mean, standard deviation, and dependent t-test. The results revealed that: 1) the efficiency of the lesson plan was 80.33/83.98, which exceeded the established criterion of 80/80; 2) students’ average achievement score increased from 14.63 before instruction to 25.16 after instruction, with the post-test score being significantly higher than the pre-test score at the .05 level; and 3) students’ overall satisfaction with the lesson plan was at the highest level (x̄ = 4.57). Among the evaluated aspects, assessment and evaluation received the highest mean score (x̄ = 4.75), followed by instructional media and equipment (x̄ = 4.63), content (x̄ = 4.54), and learning activities (x̄ = 4.38). The findings indicate that the Computer-Assisted Instruction lesson plan effectively enhanced students’ summary writing skills and generated a high level of learner satisfaction.